الكتابة الإلكترونية والتوقيع الإلكتروني وحجيتهما في الإثبات - Yousif Mohamed Ahmed Alnaqbi; Syahirah Binti Abdul Shukor; Hussein 'Azeemi Abdullah Thaidi (World Conferences Net, 2024)
The technological development has resulted in the means of communication and information; To conclude a contract remotely, which was not previously known. The electronic contract is one of the contracts that are contracted remotely; Where the technology of electronic contracts allows contracting over the network to obtain services and goods from any location or source of suppliers. It opened the way to concluding ecommerce contracts via the Internet. Through communication networks, contractors by individuals, companies or institution negotiate quickly in a virtual council. The problem lies in the fact that these contracts require more caution than traditional contracts, because the parties to the contract are not present in the contract council, which may lead to injustice, or the incorrectness of the data on the elements of satisfaction and the eligibility of the contractors. The traditional legal rules relating to the conclusion of contracts, nullity of the contract, its effects or its conclusion, and methods of proof; Does not meet the requirements of electronic contracts. Therefore, the research aims to discuss: the authenticity of electronic writing, and the authenticity of electronic signature in evidence. Through the descriptive analytical approach, the results indicated: The use of the electronic signature, especially its digital signature, to prove electronic contracts is in accordance with the principles of proof in most of the legislations that do not limit the means of proof. The legal basis available to both parties to the contract in the event of a dispute is electronic messages.